(untitled) (Research, Society and Development, 2022)
Pets, such as dogs and cats, are often affected by endoparasite infections; most of them can be transmitted to humans and become a serious public health issue in Brazil. The transmission and prevalence of intestinal parasites are directly linked to population’s hygienic-sanitary and socioeconomic conditions. Ancylostoma spp., Toxocara spp., Dipylidium caninum and Giardia spp. stand out among the main zoonotic parasites. Thus, the aims of the present study are to perform a literature review on studies focused on investigating the main endoparasite infections affecting dogs, which are seen as zoonoses, as well as to compare endoparasite infection-prevalence data between domestic and non-domestic animals. In total, 16 articles were analyzed after a systematic literature review was conducted on electronic scientific databases, such as Scopus, PubMed, Scielo and Scholar Google, which were retrospectively consulted for studies published dating back to 2000. The analyzed studies enabled observing higher incidence of parasitic infections in animals living in kennels and shelters. However, domestic animals have also shown high parasite infection rates, a fact that emphasized the important role played by disease control and prevention programs.